A highly sensitive morin sensor based on PEDT–Au/rGO nanocomposites modified glassy carbon electrode. Issue 75 (11th October 2017) - Cheng, Wenxue; Liu, Peng; Zhang, Min; Huang, Jianzhi; Cheng, Faliang; Wang, Lishi
Abstract : A facilely prepared PEDT–Au/rGO/GC sensor shows high sensitivity for electrochemical determination of morin. Abstract : In this work, we fabricated a sensitive electrochemical sensor based on a PEDT–Au/reduced graphene oxide nanocomposites (PEDT–Au/rGO) modified glassy carbon electrode (PEDT–Au/rGO/GCE) for electrochemical determination of morin. A facile, effective and high-efficiency one-pot method was employed to synthesize the PEDT–Au/rGO nanocomposites. The morphology and structure of as-prepared PEDT–Au/rGO nanocomposites were characterized by using a scanning electron microscope (SEM), transmission electron microscope (TEM) and X-ray spectroscopy (EDS), and its electrochemical characteristics were studied by EIS, CV and SWV. The PEDT–Au/rGO nanocomposites modified electrode exhibited excellent catalytic activities for morin oxidation, which was attributed to the synergistic catalytic effect that occurred at the interface of PEDT–Au and rGO layers. The effects of square wave voltammetry (SWV) parameters, accumulation time, accumulation potential and pH of the supporting electrolyte for morin were optimized. At the optimal experimental conditions, the PEDT–Au/rGO/GCE presented a high sensitivity of 0.0083 μmol dm −3 and a wide linear range from 1 to 150 μmol dm −3 toward morin oxidation with satisfactory selectivity and stability.